The main factors affecting cultural exchange between Korea and China: A semantic network analysis based on the cultural governance perspective. (July 2019) - Park, Sang Do; Lee, Jong Youl; Wang, Bo
Abstract: The cultural exchange paradigm evolved into cultural governance because of recent changes in the cultural exchange environment. This resulted in the diversification of cultural exchange subjects, the multi-channelization of methods, and diversification of contents; furthermore, cooperation between government and private sector has become particularly important in the cultural exchange process. This study examines influential factors in the cultural exchange between Korea and China from the perspective of cultural governance. To accomplish this, we collect text data on the cultural exchange between the two countries and conduct text mining. We then perform semantic network analysis and ego network analysis by selecting 80 major words included in the data collected from the digital portals of both countries. The results show that cultural exchange between Korea and China has transformed from government-led initiatives into private sector ones with information, communication, and technology-based platforms as important channels. For example, in the Korean channel, the "Korean Wave" played a central role in cultural exchange, whereas in the Chinese channel, the capacities of civilians and government agencies were the main factors. Moreover, cultural exchange between the two countries has been expanding, thus indicating the increasing importance of civilians and private platforms in cultural governance.